تأثير حجم بذور الفول السوداني ورش النباتات بخميرة الخبز ( Saccharomyces cerevisiae) في نمو وإنتاجية النبات - عبد العزيز, محمد; صارم, سناء; الشيخ, سناء (Latakia University Journal -Biological Sciences Series, 2018)
The research was carried out during 2015 and 2016 agricultural seasons Arb-ELmalk village, Banias area,Tartous Govenator to study the effect of seeds size ,peanut (Mixture , small , Medem and large) and spraying plants with three bread yeast teames (Kontrol ,once and Twice ) on germination seeds , plants height , number branches , plant , number pods plants , number seeds/ pod and pods yield ( kg. ha-1) ,The experiment design , was set split plot in a randomized complete block With four replication ,saiz seeds cosider Maine and spraying yeast sub plots , The result showed that .The saiz seeds of mixture, meduem and large are gaves significaly increased on germinations seeds , plant height , number pods/ plant and yied dray pods k.g/ha-1 on another hand goodness branches number , seeds number /pod but there were not significat increase .The once and twice spraing yeast gaves significantly increase at all characteristic mentioned above compared to the control , and the spraing twice gave butter value . 24.21- 25.20 branches/plant , 37.77-38.88 pod/plant , 2.09-2018 seeds/pod , respectivily the tow research seasons .The interaction between size seeds and spraing yeast gave significaly seeds increased at tall studies characterslices reach to 38.08-38.98 pods/plant , 2.21-2.14 seeds / pod and 4538-4598( kg.ha-1) dry pods per interactions between large ( size seeds x twic spraying) yeast during the Tow seasons respectively, on another hand there were decreased yield pods to 2700-2628( kg. ha-1) dry pod per interaction between (small size x control) .There were not signification effect of seasons agriculturl at all studies characteristic's. نفذ البحث خلال الموسمين الزراعيين 2015- 2016 في قرية عرب الملك بمنطقة بانياس لدراسة تأثير حجم بذور الفول السوداني (مختلطة، صغيرة، متوسطة، كبيرة) و رش النباتات بخميرة الخبز ( شاهد بدون رش، الرش مرة، الرش مرتين) في نسبة الإنبات وبعض صفات النمو الخضري والثمري كارتفاع النبات وعدد الفروع الثمرية، وعدد القرون / النبات، وعدد البذور /القرن والإنتاجية من القرون الجافة كغ/ هـ . استخدم تصميم القطع المنشفة إذ شغلت أحجام البذور القطع الرئيسية، وعدد الراشات القطع الثانوية وتم توزيع المعاملات عشوائياً في أربعة مكررات. بينت الدراسة النتائج الآتية : أظهر حجم البذور تأثيراً معنوياً في نسبة الإنبات, وارتفاع النبات، وعدد القرون /نبات، وإنتاجية القرون الجافة كغ /هـ بينما تحسن عدد الفروع الجانبية/ نبات، وعدد البذور /قرن ولكن بفروق غير معنوية خلال موسمي البحث. أعطى الرش مرة ومرتين فروقاً معنوية في كافة الصفات المذكورة أعلاه مقارنة مع الشاهد وأعطى الرش مرتين أفضل القيم 24.21 -25.2 فرع/ نبات و 37.77- 38.88قرن/نبات و 2.09-2.18 بذرة/ قرن على التوالي لموسمي البحث. أعطى التداخل بين حجم البذور وعدد الرشات بالخميرة تأثيراً إيجابياً ومعنوياً في كافة المؤشرات المدروسة 38.88-38.98قرن/ نبات و 2.22-2.14بذرة/ قرن و 4538-4598 كغ/هـ قرون جافة عند التداخل بين (البذور كبيرة الحجم مع الرش مرتين) خلال موسمي البحث على التوالي، وبالمقابل وجدت أقل إنتاجية 2700-2628 كغ/هـ عند تفاعل (البذور صغيرة الحجم X الشاهد بدون رش) . لم يكن للموسم الزراعي تأثير معنوي في اختلاف المؤشرات المدروسة، والفروقات التي وجدت كانت ظاهرية وغير معنوية عند المستوى 5%.